The effect of the concentration strategy for serious creativity on productive thinking, performance and accuracy of volleyball transmission skill among students - Abdel Salam , Hind (Journal of Physical Education, 2025)
This study aims to build a volleyball produced thinking, preparing educational exercises in volleyball with a focus strategy for serious creativity, and to identify the strategy of focusing for serious creativity in productive thinking and the performance and accuracy of the skill of transmitting volleyball for students, and the two assumptions were that there are statistically significant differences between the results Tribal and posttests for the experimental and controlled research groups in productive thinking and the performance and accuracy of the skill of volleyball, and there are statistically significant differences between the results of the dimensional tests of the experimental and controlled research groups in productive thinking and the performance and accuracy of the skill in volleyball, and the experimental approach was adopted by the design of the experimental and control groups, on ( 70) A student from the fourth preparatory grade from the exception of the excelling representing (42,424 %) of this society, A scale for the volleyball produced and the employment of the strategy vocabulary was built with educational exercises and applied in the practical lesson in volleyball by (3) practical lessons for performance and (1) lesson for its accuracy and a total of (4) lessons, at the rate of lesson (1) one per week, and it continued for a period of (4 Weeks, and the search procedures for the duration of (12/2/2024) continued until (3/25/2024) and after the completion of the research experience, the results were addressed with (SPSS) system to form the conclusions and recommendations that the employment of educational exercises for volleyball with the vocabulary of the focus strategy for serious creativity in practical lessons Fourth preparatory students, Its application helps in improving the level of volleyball produced, and in improving the performance and accuracy of the transmission skill facing the bottom of the volleyball for students who study it, and by superiority over their peers who study without it, and it is necessary when adopting mental measurement, especially the volleyball produced for each student in lessons The process to support improving the performance and accuracy of the transmission skill facing from the bottom in volleyball, and it is necessary not to exaggerate the importance of the cognitive structure and focus on practice and repetition in improving the performance and accuracy of the transmission skill facing from the bottom in volleyball in the center of good use of focus for serious creativity in drawing motor programs for that skill performance and accuracy.